Pembentukan Moral dan Spiritualitas Berbasis Pusat Pengembangan Anak (PPA) - Wolter Weol; Aljuanika Ering; Novelia Kaligis; Satria Mahardhika (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2022)
This study was to determine, describe and analyze the formation of moral and spirituality based on the "Kuria" child development center in adolescents in Poopoh Village, Tombariri District, Kab. Minahasa. This study uses a qualitative (descriptive) approach which was carried out at PPA “Kuria” Poopoh 2021. The data collected through observation, interviews, and documentation have been analyzed and resulted that (1) the formation of morals and spirituality in adolescents has been maximized with the existence of several programs such as retreats, discipleship, bible camp, recording, memorizing verses and other programs; (2) These programs are carried out by following the schedule determined by the staff, usually 2 meetings a week and for other programs carried out during holidays; (3) The existence of supporting factors, namely cooperation between mentors, staff and parents in supporting the program to run well; (4) As well as the existence of inhibiting factors from within teenagers who have been affected by technological sophistication such as online games and the environment; (5) The efforts made were very good, namely by approaching and trying to be friends with the children. From the data findings and research results, it is recommended for staff and mentors as well as parents to continue to control the association of children and provide coaching and more creative programs to attract children's attention in activities.